Essence of contracts concluded for implementing corporate investment (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The article is focused on clarifying the essence of contracts in the field of corporate investment. Achieving the specified purpose is realized through the analysis of the relevant norms of the current legislation of Ukraine, court case-law and provisions of the legal doctrine, which is the objective of this article.It has been emphasized that investment contracts cover various types of civil contracts. It has been determined by the subject matter and objectives of investment (joint operation agreements, capital construction contracts, credit granting agreements, purchase and sale agreements, fiduciary management agreements).The contract is the main form of investing in the field of corporate legal relations. The author has substantiated the specific features of such a contract, which are: the special sphere of its application; special contracting parties.The sphere of application of the contracts studied in the article is corporate legal relations, that is, relations connected to the exercise of corporate rights to participate in the management of a business entity. The parties to the contract in the field of corporate investment are the subjects of investment operation, which primarily include: an investor, i.e., the subject of investment operation that makes a decision to invest own, loaned and borrowed property and intellectual values into investment objects. The other party to the contract can be, in particular, a corporate fund, assets management company as recipients of investments.Such contracts are not united by a common subject matter, which is determined by a specific type of investment contract (asset management actions, a share in the authorized (joint) capital of a business entity, etc.). Therefore, the author has emphasized the impracticality of uniting contracts in the field of corporate investment into a separate group of civil contracts. Contracts concluded for the purpose of implementing corporate investment are consensual, commutative and bilateral.
Keywords: contract; investment contract; investments; investment operation; corporate legal relations; equity fund.